(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This study presents findings related related to the design of a Virtual Learning Environment (VLE) that incorporates the interactive reading approach to enhance English text comprehension in 6th- grade students at the Francisco José de Caldas School in the municipality of Pandi, Cundinamarca. The research is based on a qualitative approach and the principles of action research. The design of the VLE integrates technological, cognitive, and pedagogical-didactic components interdependently. Preliminary results demonstrate significant improvements in English reading comprehension, highlighting the effectiveness of this design in the educational process. This research shows a diverse potential of strategies to effectively address difficulties in English reading comprehension in secondary education students.